2019
DOI: 10.22616/rrd.25.2019.032
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a headspace solid–phase microextraction with different fibres for volatile compound determination in specialty coffee brews

Abstract: The aroma of coffee is the main quality factor. Compounds with floral, fruity, citrus and sometimes fermented aroma notes are defined as high quality characteristics for the specialty coffee brew. Commercial coffees mostly are at medium roast and the aroma profile is focused on balanced chocolate, caramel, toasted bread and almond bitterness aroma notes. These sensory characteristics set the focus for volatile compound profile analysis by Headspace solidphase microextraction (HS-SPME). The most popular fibres … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Each marine bacteria sample was analyzed three times using the DVB/CAR/PDMS coating solid-phase microextraction fiber; 37 °C extraction temperature; and 40 min extraction time. DVB/CAR/PDMS fiber was selected due to its high capacity for the extraction of volatile and semi-volatile compounds present in samples [ 21 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Each marine bacteria sample was analyzed three times using the DVB/CAR/PDMS coating solid-phase microextraction fiber; 37 °C extraction temperature; and 40 min extraction time. DVB/CAR/PDMS fiber was selected due to its high capacity for the extraction of volatile and semi-volatile compounds present in samples [ 21 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lee et al (2017) 49 evaluated the effect of the reverse process of grinding and roasting coffee on volatile compounds profiles, identifying 50 compounds in coffee roasted with the conventional method and 39 using the reverse method of grinding and roasting. To Laukaleja et al (2019) 55 , main volatile compounds were furans, pyrazines, aldehydes and ketones, attributing to the last three an association with a pleasant aroma and flavor in specialty coffees. Heo et al (2020) 56 identified 36 volatile compounds, highlighting that the extraction method and temperature could influence the volatile compound profiles.…”
Section: Chemical Composition Of Specialty Coffee Beans (Coffea Arabi...mentioning
confidence: 94%
“…Volatile compounds were extracted by solid-phase microextraction (SPME) with 50/30 μm divinylbenzene/carboxen/poly(dimethylsiloxane) (DVB/CAR/PDMS) fiber (Stableflex, 23Ga, Autosampler) (Supelco, Bellafonte, PA). The SPME parameters were chosen according to Gloess et al (2013), with some modifications (Laukaleja & Kruma, 2019a).…”
Section: Hs-spme and Gc-ms-o Analysismentioning
confidence: 99%
“…Although it is important to note that specific volatile compound detection in coffee brews can be influenced by different SPME fibers. Carboxen/PDMS (CAR/PDMS) and divinylbenzene/carboxen/ PDMS (DVB/CAR/PDMS) fibers are reported as most suitable for coffee brew volatile compound extraction (Laukaleja & Kruma, 2019a;Oliveira, Oliveira, Franca, & Augusti, 2009;Rubio, Sanllorente, Sarabia, & Ortiz, 2014).…”
Section: Introductionmentioning
confidence: 99%